The Impact of Forensic Accounting on Tax Payer Attitude and Compliance Towards Tax Evasion Within SMEs in The North East Nigeria - Haruna, Haruna Tijjani; Ibrahim, Abdulrazaq Suleiman; Yusuf, Abubakar Usman; Ardo, Abu Mohammed (UUM Press, 2023)
Income tax has contributed to a considerable amount of Nigeria’s revenue generation, despite the fact that it is fraught with difficulties in both collection and execution. This study examines the impact of forensic accounting on tax payer attitude and compliance towards tax evasion within SMEs in the north east Nigeria. The study is cross- sectional, with data collected using simple random sampling. With the help of Smart PLS 3, partial least square structural equation modelling PLS-SEM on 102 responses was utilized to evaluate the data. The findings revealed that a forensic accounting check is required to address the issue of tax evasion in Nigeria to ensure a good attitude and compliance. Forensic Accounting (FA) improves Tax payers Attitude (TA) and Tax Compliance (TC) when they interact. Hence, when a taxpayer develops a positive attitude and comply with the tax laws, they are more likely to have a good financial record and the state would have better control over the tax evasion scale. In other words, small and medium enterprises (SMEs) in the Northeast are more inclined to tax commitment if they are checked, and if the government use their contributions toward improving their standard of living, this will develop a positive attitude toward the behaviour of taxpayers in the region. Therefore, the government should provide awareness on the uses of tax revenue through sustainable enterprise support, infrastructure, and social welfare.